Proceso de ASC - GENERACION Y ALMACENAMIENTO DE ENERGIA TERMOQUIMICA (2020)
The project consisted of the development of low-cost renewable energy generation and storage devices. The study and development of solar concentrators was proposed, that is, devices capable of concentrating the energy from sunlight in a specific area for its use. Additionally, the design and implementation of rechargeable redox flow batteries capable of storing the energy produced by concave solar concentrators was proposed.